Analisis Tingkat Kesejahteraan Rumah Tangga Nelayan Berdasarkan Nilai Tukar Nelayan (NTN) di Kecamatan Cilincing Jakarta Utara - Dina Wahyuni; Abubakar Abubakar; Luthfi Nur’azkiya (Peneliti.net, 2022)
Cilincing sub-district is one of the sub-districts that is directly adjacent to the coastal area of DKI Jakarta. The impact of reclamation, water pollution, and weather factors affects the income and the level of welfare of fishermen's households. The purpose of the study was to determine the income from capture fisheries and non-fishery, determine the food and non-food expenditures and determine the welfare level of fishermen's households based on the fishermen's exchange rate in March 2022 in Cilincing District, North Jakarta. The research method used is the survey method, and this research uses quantitative descriptive research. The sampling technique used purposive sampling with respondents as many as 44 fishermen who own boats with a maximum size of 10 gross tons who live in Cilincing District, North Jakarta. This study uses primary and secondary data. Primary data were obtained from interviews using questionnaires and secondary data obtained from related agencies. The results showed that the average income of capture fisheries and non-fishery were Rp2.512.372 and Rp437.589, respectively. The average food and non-food expenditures were Rp1.491.511 and Rp872.536, respectively. The average fishermen's exchange rate in March 2022 is 1,25. This shows that fishers can meet primary and non-primary needs.